Demand for green finance: Resolving financing constraints on green innovation in China - Yu, Chin-Hsien; Wu, Xiuqin; Zhang, Dayong; Chen, Shi; Zhao, Jinsong (Energy policy, 2021)
This paper investigates the effects of financing constraints on prompting green innovations using a sample of Chinese listed firms in the period 2001–2017. Also, we explore how green finance policies resolve financing constraints of firms to green innovation. The capability of green innovation is found to be impaired when firms face higher financing constraints, and privately owned enterprises tend to be more vulnerable than state-owned ones in this regard. Although green finance policies can effectively ease financing restraints on green innovation overall, green credits are less likely to be available to privately owned enterprises. However, these enterprises which are deeply affected by financing constraints have relatively high innovation capabilities. We suggest the government to provide more supports to privately owned enterprises for investing in green projects. Further, both financial institutions and privately owned enterprises should be required to disclose more information on green credits and green projects, respectively. In addition, the China Banking Regulatory Commission should design a synthetic mechanism for evaluating green performance. •Green innovation is impaired when firms face higher financing constraints.•Green finance policies effectively alleviate the effects of financing constraints.•Green finance policies seem unable to benefit privately owned enterprises.